Handbook of temporal reasoning in artificial intelligence - Fisher, Michael, 1962-; Gabbay, Dov M., 1945-; Vila, L. (Lluis) (Amsterdam ; Boston : Elsevier, 2005)
This collection represents the primary reference work for researchers and students in the area of Temporal Reasoning in Artificial Intelligence. Temporal reasoning has a vital role to play in many areas, particularly Artificial Intelligence. Yet, until now, there has been no single volume collecting together the breadth of work in this area. This collection brings together the leading researchers in a range of relevant areas and provides an coherent description of the breadth of activity concerning temporal reasoning in the filed of Artificial Intelligence. Key Features: - Broad range: foundations; techniques and applications - Leading researchers around the world have written the chapters - Covers many vital applications - Source book for Artificial Intelligence, temporal reasoning - Approaches provide foundation for many future software systems Broad range: foundations; techniques and applications Leading researchers around the world have written the chapters Covers many vital applications Source book for Artificial Intelligence, temporal reasoning Approaches provide foundation for many future software systems.
Formal theories of time and temporal incidence / Lluis Vila -- Eventualities / Antony Galton -- Time granularity / Jβerγome Euzenat and Angelo Montanari -- Modal varieties of temporal logic / Howard Barringer and Dov Gabbay -- Temporal qualification in artificial intelligence / Han Reichgelt and Lluis Vila -- Computational complexity of temporal constraint problems / Thomas Drakengren and Peter Jonsson -- Indefinite constraint databases with temporal information : representational power and computational complexity / Manolis Koubarakis -- Processing qualitative temporal constraints / Alfonso Gerevini -- Theorem-proving for discrete temporal logic / Mark Reynolds and Clare Dixon -- Probabilistic temporal reasoning / Steve Hanks and David Madigan -- Temporal reasoning with iff-abduction / Marc Denecker and Kristof Van Belleghem -- Temporal description logics / Alessandro Artale and Enrico Franconi -- Logic programming and reasoning about actions / Chitta Baral and Michael Gelfond -- Temporal databases / Jan Chomicki and David Toman -- Temporal reasoning in agent-based systems / Michael Fisher and Michael Wooldridge -- Time in planning / Maria Fox and Derek Long -- Time in automated legal reasoning / Lluis Vila and Hajime Yoshino -- Temporal reasoning in natural language / Alice ter Meulen -- Temporal reasoning in medicine / Elpida Keravnou and Yuval Shahar -- Time in qualitative simulation / Dan Clancy and Benjamin Kuipers.
Includes bibliographical references (p. 665-722) and index.
Keywords: Temporal databases; Artificial intelligence; Reasoning; Electronic books